Role of HBV replication in host cell metabolism : a proteomics and metabolomics analysis - Laleh Sadrolodabaee (2014)
Hepatocellular carcinoma (HCC) with more than 700,000 deaths every year is the most prevalent type of liver cancer and a global concern. It has a poor general prognosis and low survival rate, hence improving HCC therapy is highly important. HCC is mainly developed as the result of chronic hepatitis B virus (HBV) infection. It is estimated that about 53% of HCC patients are afflicted with chronic HBV. The smallest protein of HBV, HBx, has vital role in hepatocellular carcinogenesis. In this study, we aim to investigate the association between HBV replication and the host cell metabolism. Rat primary hepatocytes (RPHs) and human hepatocellular liver carcinoma (HepG2) cells were transfected with different genotypes of HBx. Total proteins and metabolites were extracted and analyzed using LC-MS/MS and GC-MS. LC-MS/MS based proteomics and GC-MS based metabolomics were applied in order to establish a comprehensive cellular proteomic as well as metabolomic profiling of HBx transfected cells. The iTRAQ-coupled LC-MS/MS results indicated that a number of glycolytic enzymes including lactate dehydrogenase (LDH), Hexokinase (HK), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), phosphoglycerate kinase (PGK) and pyruvate kinase (PK) were significantly up-regulated while two TCA cycle enzymes, succinate dehydrogenase (SDH) and fumarate hydratase (FH) were down-regulated in RPHs and HepG2 cells transfected by HBx compared to the pXJ40 control group. These findings suggested that HBV replication could alter host cell metabolism by reducing TCA cycle and increasing the rate of glycolysis to provide important metabolic requirements for nucleotides, amino acids and lipids synthesis. Our proteomics approach may provide candidate biomarkers which improves insights into the future of HBV-associated HCC diagnosis. In addition, iTRAQ-coupled LC-MS/MS was applied in order to investigate the role of SH3 binding domain in virus-host interactions. For this purpose, four proline residues at proline rich region of HBx were converted to alanine. Comparing the protein profile of wild type HBx and P-A mutant HBx, may provide valuable information on the role of SH3 binding domain in virus-host interactions. Our findings demonstrated that a series of differentially expressed cellular cytoskeletal and signaling proteins including vimentin and annexin A2 may interfere with HBx via its proline rich domain. These differentially expressed cellular proteins play a significant role in cytoskeleton organization and cell migration which are involved in hepatocellular carcinogenesis. As a complement to our proteomics approach, metabolomic analysis was applied to explore the relevance of our proteomics data. GC-MS based metabolomics was carried out to analyze the intracellular metabolites in HepG2 cells transfected by different genotypes of HBx. In our metabolomic profiling, a total of 71 metabolites were identified out of which 10 showed significant changes compared to the control group. Lactic acid, succinic acid, glucose 6-phosphate, valine, glycine, proline, alanine and glutamate were significantly up-regulated while palmitic acid and stearic acid were down-regulated in HBx transfected HepG2 cells. These metabolites are involved in several key metabolic pathways such as glycolysis, glutaminolysis, TCA cycle, amino acids and fatty acids metabolism. Our comprehensive metabolomic profiling of HBx transfected cells may indicate differentially expressed metabolites for developing potential biomarkers which could improve antiviral strategies, thus better managing HBV-related HCC patients. Taken together, the combined proteomics and metabolomics information on the status of HBx transfected cells provides a comprehensive understanding on the role of HBV replication in host cell metabolism and may improve therapeutic strategies for HBV- associated HCC.